Old Icelandic consonant lengthening rule and modern Icelandic infixation of /d - Janez Orešnik (Linguistica, 1973)
Old Icelandic had a Consonant Lengthening Rule in its morphological component, whose task was to lengthen postvocalic stem final l, n, s in certain inflexional forms, e.g. in the nom. sg. stóll of stól- "chair". The rule is formulated in § 1.1, and illustrated in § 1.2, where some of its exceptions are listed as well. The formulation of the rule presented in § 1.1 is defended· in some detail in § 1.3.In § 1.4 the ordering relations of the rule are discussed (it operates earlier than any phonological rule), and in § 1.5 its gradual disappearance from the language is described.